Numerical Analysis of the Response of Existing Tunnel Structures to Crossing Tunnel Construction in Soft Soil - Yanreginata, Muhammad Amhar Wajdi; Prakoso, Widjojo Adi (Universitas Ibn Khaldun Bogor, 2024)
Massive urban planning forces the utilization of underground space, not least in the development of transportation infrastructure. MRT Jakarta has successfully made its line in phase 1 Lebak Bulus - Bundaran HI and now is developing the line which is packaged in phase 2 to the direction of Ancol, this route reaches the south-north part of Jakarta. In recent years, there has also been a plan to add an East-West line which will be packed in phase 3, this does not rule out the possibility of a meeting between the existing tunnel and the undercrossing tunnel. This study discusses the influence of undercrossing on the existing tunnel structures, especially under Jakarta Clay, which is classified as having a thick, soft clay stratum. This research was divided into 2 steps using finite element analysis with Hardening Soil model. The first step is to conduct a back analysis to obtain the actual soil parameter value then proceed with step 2, which is to conduct an undercrossing twin tunnel analysis. Based on the results of the study showed the fittest soil parameters using the correlation E50 = 3500N by the effective soil strength parameters and the undercrossing excavation caused four stages of vertical displacement of the existing tunnel.